Hazard Identification, Risk Assessment, and Determining Control (HIRADC) for Workplace Safety in Manufacturing Industry: A Risk-Control Framework Complete with Bibliometric Literature Review Analysis to Support Sustainable Development Goals (SDGs) - H. Henny; Agus Heri Setya Budi; Muhammad Andriyansyah; Muhammad Rizzki Ar Rozzak; Maretno Marcelina Baru; Alias Masek (ASEAN Journal for Science and Engineering in Materials, 2025)
This study implements the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method to evaluate and mitigate occupational risks in the manufacturing construction sector. A bibliometric analysis reveals a growing yet insufficient number of studies applying structured risk control frameworks like HIRADC in industrial settings, particularly in developing countries. Using a descriptive approach, data were collected through field observations, interviews, and document analysis. Seven hazards were identified, resulting in five low-risk and two moderate-risk classifications using a probability–severity matrix. Control measures were implemented following ISO 45001:2018 standards, including engineering controls, administrative actions, and personal protective equipment (PPE). The results demonstrate that HIRADC enhances workplace safety awareness and reduces risk levels. This study contributes a practical safety framework for manufacturing environments while reinforcing the relevance of SDG-aligned and bibliometrically justified research in occupational health.